Transforming Alliances: A 20-Year Overview of Singapore-US Relations under Lee Hsien Loong - TRUONG HUE (مجلة الدراسات الاجتماعية)
The strategic relationship between Singapore and the United States has seen significant growth, especially under Prime Minister Lee Hsien Loong’s leadership. Over the past two decades, their bilateral ties have been strengthened through collaboration in defense, trade, and security, with key agreements like the 2005 Strategic Framework Agreement and the renewal of the 1990 Memorandum of Understanding on U.S. military access to Singaporean facilities. These agreements have cemented Singapore’s role as a crucial partner in U.S. Indo-Pacific strategy. This paper analyzes the key milestones and mechanisms that have bolstered Singapore-U.S. relations under Lee’s leadership, focusing on the creation of the Singapore-U.S. Strategic Dialogue, which added a new dimension to the partnership beyond trade and defense. It also examines how both countries have expanded their cooperation into non-traditional security areas such as counterterrorism, cybersecurity, and environmental security, adapting to the evolving global security environment. By exploring these developments, the paper demonstrates how the Singapore-U.S. partnership has diversified and deepened in response to emerging global challenges. It also evaluates how these efforts culminated in the 2015 elevation of the relationship to a Strategic Partnership, promoting more dynamic and comprehensive collaboration. Ultimately, the study highlights the mutual benefits of this strengthened partnership, contributing to regional stability, economic prosperity, and global security.